ANALISIS PERBANDINGAN RUANG DAN WAKTU ALGORITMA ENKRIPSI BLOWFISH DAN TWOFISH PADA ENKRIPSI DAN DESKRIPSI BERKAS MENGGUNAKAN MODUL PYTHON - Candra Kurniawan; Mochammad Fadhli Magfur; Fauziah Fauziah (E-Link: Jurnal Teknik Elektro dan Informatika, 2024)
The rapid development of information technology is accompanied by an increase in cyber incidents such as data breaches. One of the security methods that can be implemented to enhance data security against data breaches is by applying cryptography to data management systems. Cryptography is useful for encrypting plaintext into ciphertext, making the data not easily readable. One of the encryption algorithms widely used in data security is Blowfish and Twofish. Blowfish and Twofish are symmetric encryption algorithms that use a single key for encryption and decryption. This journal focuses on testing the encryption and decryption of Blowfish and Twofish algorithms in relation to space and time complexity. The results of testing three sets of data on two different devices indicate that the Blowfish algorithm has better speed than Twofish, while Twofish performs better than Blowfish in terms of memory usage. Moreover, the usage of the processor affects the speed of the process.